Innovation in real places strategies for prosperity in an unforgiving world - Breznitz, Dan. (Oxford University Press Oxford University Press, 2021)
Across the world, cities and regions have wasted trillions of dollars on blindly copying the Silicon Valley model of growth creation. Since the early years of the information age, we've been told that economic growth derives from harnessing technological innovation. To do this, places must create good education systems, partner with local research universities, and attract innovative hi-tech firms. We have lived with this system for decades, and the result is clear: a small number of regions and cities at the top of the high-tech industry but many more fighting a losing battle to retain economic dynamism.
Includes bibliographical references and index.
Keywords: Technological innovations--Economic aspects